Evaluation of PV, Wind, Diesel Hybrid Energy Potential for GSM Tower in Myanmar - Zin Mar Nyo (Institute of Advanced Engineering and Science, 2015)
Not only GSM, WCDMA but also CDMA technology can be used in Myanmar but GSM pre-dominates in the market. There are over million unique subscribers across the country in 2013. Power supply for telecom becomes main challenges in Myanmar where the electricity can not access in rural area. To minimize deficit of power, the government has set a target to covert some of tower sites to renewable solutions by 2015. This paper proposes the use of a PV, wind and diesel generator hybrid system with storage element in order to determine the optimal configuration of renewable energy in Myanmar. This paper discusses the development of a renewable energy sources (RES) that can be used for electric power supply of GSM base station site at any given time and considers the feasibility of developing Solar (photovoltaic)-Wind-Diesel hybrid power systems for supplying electricity to off-grid rural telecommunication. The Hybrid Optimization Model for Electric Renewables (HOMER) was used to simulate and generate feasible solution through combinations of photovoltaic, Wind Turbines and Diesel Generator with a minimum levelised cost of electricity supply and to determine the technical feasibility of the system.